(untitled) (Central Medical College Journal, 2025)
Background: Smokeless tobacco (SLT) consumption is culturally practiced in Bangladesh. Despite its popularity, inadequate information is available on SLT usage. The common belief among the consumers of smokeless tobacco is that is not as hazardous as smoking tobacco. Objective: To assess the patterns and attitudes toward smokeless tobacco consumption among women in a rural setting. Methods: The cross-sectional study is conducted over ten days among 288 women in Sreemantapur rural area at Sadar South Upazilla under Cumilla district. Respondents are choosed by convenience sampling technique; data collection method is face-to-face interview with a semi-structured questionnaire. Results: Out of 288 respondents, the majority (37.5%) of the participant’s age is <30 years. Most of them (96.5%) are housewives and 27.8% are educated up to secondary level. About the consumption of SLT, 24.3% of the participants consume SLT among them 48.3% consume Zarda and 37.5% of Zarda consumers have been consuming it for 6-10 years. Regarding the suffering of the participants, 67.1% of SLT consumers report that they suffer if they do not consume SLT. Regarding attitude towards smokeless tobacco, 93.4% of our respondents believe that SLT use is not acceptable for women in society, 96.2% and 94.8% agreed that women using SLT harms their health and smokeless tobacco is addictive respectively. Conclusion: Our data suggests that the attitude towards SLT among women in rural setting is satisfactory but there is still a prevalence of SLT consumption. National wide campaign activities should be conducted elaborately to raise awareness among rural women to reduce smokeless tobacco use. Central Medical College Journal Vol 8 No 2 July 2024 Page: 58-63